A registry of HLA‐typed donors for production of virus‐specific CD4 and CD8 T lymphocytes for adoptive reconstitution of immune‐compromised patients. Issue 12 (20th July 2014) - Li Pira, Giuseppina; Ivaldi, Federico; Starc, Nadia; Landi, Fabiola; Rutella, Sergio; Locatelli, Franco; Sacchi, Nicoletta; Tripodi, Gino; Manca, Fabrizio
<x xml:space="preserve">Abstract</x> Background Virus‐specific CD4 and CD8 T lymphocytes from HLA‐matched donors are effective for treatment and prophylaxis of viral infections in immune‐compromised recipients of hematopoietic stem cell transplant recipients. Adoptive immune reconstitution is based on selection of specific T cells or on generation of specific T‐cell lines from the graft donor. Unfortunately, the graft donor is not always immune to the relevant pathogen or the graft donor may not be available (registry‐derived or cord blood donors). Study Design and Methods Since the possibility of using T cells from a third‐party subject is now established, we screened potential donors for T‐cell responses against cytomegalovirus (CMV), Epstein‐Barr virus (EBV), and adenovirus, the viruses most frequently targeted by adoptive immune reconstitution. Specific T‐cell responses against viral antigens were analyzed in 111 donors using a miniaturized interferon‐γ release assay. Results Responders to CMV were 64%, to EBV 40%, and to adenovirus 51%. Simultaneous responders to the three viruses were 49%. CMV‐specific CD4 and CD8 T‐cell lines could be generated from 11 of 12 donors defined as positive responders according to the T‐cell assay. Conclusions These data demonstrate that a large fraction of volunteers can be recruited in a donor registry for selection or expansion of virus specific T cells and that our T‐cell assay predicts the donors' ability to give rise to established T‐cell lines endowed with proliferative potential and effector function for adoptive immune reconstitution.